Ketogenic Diets for Mental Illness - Dr. Saumitra Mahendra; Dr. Vertika Sharma; Dr. M. Nithya Devi; Dr. Saumitra Mahendra (International Journal of Pharma and Bio Sciences, 2024)
The ketogenic diet, characterized by its elevated fat content and reduced carbohydrate intake composition, has garnered interest due to its potential benefits on mental health disorders and influence in health risk. Early research suggests that, the ketogenic diet may have therapeutic effects on conditions such as depression, anxiety, and bipolar disorder, although further research is required to validate these discoveries. One suggested reason is the diet’s capacity to decrease oxidative stress, which is linked to the underlying causes of several mental health issues. The ketogenic diet is thought to alter the brain’s energetic matrix, leading to changes in neurotransmitter function and brain metabolism. Understanding the brain effects of the ketogenic diet could provide valuable insights into its potential as an adjunctive therapy for mental illness. Early published reviews on ketogenic diets for mental illness often overlooked the intricate relationship between diet and mental health, focusing more on traditional pharmacological treatments. There is a gap in the existing evidence on the precise impact of ketogenic diets on mental health issues, highlighting the need for a comprehensive review in this area. This article comprehensively covers the relationship between ketogenic diets and mental illness, exploring the potential benefits and side effects. It discusses how ketogenic diets may influence oxidative stress in mental health disorders and examines their effects on the brain’s energetic matrix. The article also addresses the benefits of ketogenic diets for mental health and highlights the potential side effects of ketogenic therapies. This review addresses previous lacunas by focusing on the specific effects of ketogenic diets on mental health disorders. It is timely and relevant in light of the increasing interest in alternative treatments for mental illness and health risk, providing valuable insights into the potential role of ketogenic diets in mental health care.